An analysis of playing positions in elite men's volleyball: Considerations for competition demands and physiologic characteristics - Sheppard, J. M.; Gabbett, T. J.; Stanganelli, L. -C. R. (The Journal of Strength and Conditioning Research, 2009)
The purpose of this study was to investigate the physiologic demands, physiologic characteristics, and jumping ability of different playing positions in elite male volleyball players. The first investigation involved an analysis of 16 international men's volleyball matches. The second investigation involved an analysis of the anthropometric and jump performance characteristics of 142 Development National Team (DNT) and Senior National Team (SNT) international volleyball players. Mean (±SD) frequency of block jumps for Middles (11.00 ± 3.14) was significantly greater than for Setters (6.25 ± 2.87, p < 0.001) and Outsides (6.50 ± 3.16, p < 0.001). Attack jumps were performed more frequently by Middles (7.75 ± 1.88), and this was found to be significantly more than for Setters (0.38 ± 1.06, p < 0.001) and Outsides (5.75 ± 3.25, p < 0.01). Middles were taller than Outsides and Setters (p < 0.001). Consequently, Middles had a significantly higher reach and greater body mass than Outsides (p < 0.001, p < 0.003) and Setters (p < 0.001, p < 0.001). Both Middles and Outsides had superior countermovement vertical jump (CMVJ) and spike jump (SPJ) scores compared with Setters (p < 0.001). Position-specific comparisons between DNT players and SNT players demonstrated that the SNT players were superior in relative CMVJ and SPJ scores (p < 0.05), with a large magnitude of effect (d > 0.99). The results of this study highlight the large jumping and landing demands placed on the taller and heavier players in the middle position. In addition to establishing the magnitude of difference in jumping ability between junior and senior national team players, the results also provide a comprehensive data set that may assist with talent identification and talent development for aspiring male volleyball players.